Epidemiology of laboratory-confirmed SARS-CoV-2 hospitalized cases in a tertiary hospital, Gauteng Province, South Africa, 1 April 2020 to 31 March 2021 - Sikhosana, Mpho Lerato (University of the Witwatersrand, Johannesburg, 2021)
Gauteng Province (GP) was the most affected province in South Africa during the first year of the COVID-19 pandemic. We aimed to describe the epidemiology of COVID-19 cases admitted in one of the largest quaternary hospitals in the province during the two pandemic waves. We used data from the national hospital surveillance system, DATCOV, that recorded COVID-19 admissions at Charlotte Maxeke Johannesburg Academic Hospital in (GP) from 5 March 2020 to 27 March 2021. We used multivariable logistic regression to determine a) factors associated with hospitalization in the second compared to the first pandemic wave, and b) factors associated with in-hospital mortality. There were 1861 cases admitted during the study period. The mean age of the cases was 50 (IQR 37-61), 51.80% were females, and 58.68% were black. Of the total number of admissions, 2.10% were healthcare worker, 53.85% of whom were nurses. On admission, 91.99% of cases were admitted at a general ward while 5.86% were admitted at an intensive care unit. Overall, 10.59% of the cases required intensive care during their hospital stay. The case fatality ratio was the highest (28.54%) during wave 2 and lowest during pre-wave (11.49%). Compared to the first wave, factors associated with hospitalization during the second wave included age >80 years (adjusted odds ratio [aOR] 3.43, 95% CI 1.07-10.98) compared to ages 0-19 years, as well as being of other race (aOR 5.63, 95%CI 1.84-17.20) compared with White race. Regarding in-hospital mortality, associated factors included age groups 60-79 (aOR 4.53, 95%CI 1.03-19.86) and >80 (aOR 9.63, 95%CI 1.93-48.01) compared to ages 0-19 years; male sex (aOR 1.55, 95%CI 1.16-2.08); presence of an underlying comorbidity (aOR 1.99, 95%CI 1.45-2.71) 106 as well as being admitted during the second wave (aOR 1.54, 95%CI 1.12-2.10). Our study found that there was a higher risk of mortality during the second compared to the first wave, and other factors associated with mortality included older age, being male as well as having an existing comorbidity. These findings will help inform prevention strategies required to prevent high mortality rates during future waves of infection.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Virology, to the Faculty of Science, School of Pathology, University of the Witwatersrand, Johannesburg, 2021.
Keywords: COVID-19; Hospitalisation; In-hospital mortality; Comorbidities; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education